Structure and property change of technogenic raw material samples as a result of electric pulse processing - Sakipova, S.E.; Sakipova, SH.; Nussupbekov, B.R.; Ospanova, D.; Akhmerova, K.; Khassenov, А. (Publishing House of the KarSU named after E.A.Buketov, 2014)
This paper presents the problems and prospects of application of electric pulse technology for crushing and grinding of inorganic materials. Using scanning electron microscopy, a spectral analysis of samples of technogenic raw materials from Nurkazgan field was made after mechanical grinding and after electric pulse processing. The results of X-ray spectral microanalysis, obtained by using the ZAF method, show changes in microstructure and elemental composition of the samples of industrial raw materials as a result of electric pulse processing. It was established that the technology of electric pulse crushing and grinding of inorganic materials makes it possible to obtain not only a final product with desired size of fragmented particles, but also to change their physical and chemical properties. The results of the spectral analysis show an ambiguous effect of different modes of electric pulse processing on structure and elemental composition of raw material.
Keywords: underextracted metals; technogenic raw materials; "poor" ore, electric pulse processing; spectrophotometric analysis